Research on the height of primary school students in Zhuzhou and analysis of influencing factors of short stature - Ye, Xiao-min; Tang, Qiong; Yang, Yi-can; Wen, Xiang-Lan (Frontiers in Pediatrics, 2025)
ObjectiveTo construct a growth curve for children aged 6–12 years residing in Zhuzhou, assess the height distribution among local elementary school students, and analyze the factors contributing to short stature.MethodsWe measured the heights of children from 110 elementary schools in Zhuzhou using cluster sampling. A total of 106,864 samples of children aged 6–12 years were collected and divided into 25 age groups, each spanning three months. The Lambda-Mu-Sigma (LMS) method was employed to calculate the 3rd, 10th, 25th, 50th, 75th, 90th, and 97th percentiles of height for each age group. Children below the 3rd percentile according to the national growth curve made in 2005 were considered to be short stature. The heights of boys and girls in Zhuzhou were compared with the national average heights from 2005. The height growth curve was constructed using the curve estimation function of SPSS software and the influencing factors for the prevalence of short stature were identified using logistic regression analysis based on data obtained from parental questionnaires.ResultsThe prevalence of short stature among children aged 6–12 years in Zhuzhou was found to be 3.97%. Boys exhibited a significantly higher incidence of short stature at 4.53% compared to girls at 3.37%. Children residing in suburban areas showed a notably higher prevalence of short stature (5.80%) compared to their urban counterparts (3.67%), with these disparities proving statistically significant. Logistic regression analysis identified several contributing factors for short stature in this population, including low birth weight, inadequate daily physical activity (less than 0.5 h), father's educational qualification of junior college level or below, short stature of parents, insufficient sleep duration, and male gender.ConclusionTo improve children's height in Zhuzhou, it's important for them to exercise for over 30 min daily and sleep for more than 10 h each night. Regular monitoring of growth and nutrition is crucial. Health education for families with less educated fathers and early intervention for children with short-statured parents are also key strategies.